Development of Science Handouts Based on Critical Thinking Skills on the Topic of the Human Digestive System - Ai Sulastri; Badruzsaufari Badruzsaufari; Dharmono Dharmono; Mohamad Nor Aufa; Muhammad Aditya Saputra (Jurnal Penelitian Pendidikan IPA, 2022)
Improving the achievement of competencies which are indicators in the study of the quality of education in Indonesia, can be done by procuring quality and innovative teaching materials. This study aims to develop a science learning handout on the human digestive system to improve critical thinking skills for class VIII SMP. Development is done by (Educational Design Research). This study aims to develop a science learning handout on the human digestive system to improve critical thinking skills for class VIII SMP. This article describes the results of the validity and practicality of science learning handouts on the human digestive system. The instrument used in this study was a validity and practicality questionnaire. Data analysis techniques include descriptive data analysis, validation sheets, and questionnaires. The handout validation sheet is given to 5 validators. Instead, 31 grade VIII students of SMP Negeri 5 Banjarmasin were given practice sheets. The results of the validity questionnaire analysis concluded that the validity of the handout was 3.67 very valid categories. Practicality test of content average of 87.41 was obtained in the very practical category. The results of the practicality test of expectations average of 87.78 in the very practical category. Finally, the actual practicality test results average of 85.65 with a very practical category. This means that science handouts are valid and practical in the learning process to practice critical thinking skills